Synanthropy of Bloodsucking Mosquitoes (Diptera, Culicidae) under Conditions of Kyiv - Kilochytska, N.P. (Вестник зоологии, 2012)
The 35 anthropophilic species are analyzed. The main tendancies of adaptations tending the transition of bloodsucking mosquito to synanthropic existence are considered. It is shown, that certain part of bloodsucking mosquitoes species inhabiting natural biocoenoses have been already adapted before the assimilation into the anthropogenic landscapes.